Collagen bio-stimulators in facial rejuvenation: A literature review (Research, Society and Development, 2024)
The objective of this literature review is to investigate the role of collagen biostimulators in facial harmonization, utilizing scientific articles from the PubMed, LILACS, and MEDLINE databases, as well as the SciELO electronic library. Facial harmonization is a set of aesthetic procedures aimed at improving the symmetry and proportion of facial features, reflecting a global trend in aesthetics and personal care. Collagen biostimulators are recognized for promoting the production of this essential protein for the skin's elasticity and strength. They work through a controlled inflammatory response that stimulates the synthesis of new collagen, enhancing the structure of the dermis and resulting in firmer and rejuvenated skin. The decline in collagen production with age is linked to skin aging and the loss of skin firmness. It is concluded that collagen biostimulators are an effective alternative for facial rejuvenation and the treatment of sagging, offering significant benefits in the reduction of wrinkles and fine lines.